Recent Progress in Surface-Enhanced Raman Scattering for the Detection of Chemical Contaminants in Water - Bodelón, Gustavo; Pastoriza-Santos, Isabel (Frontiers in Chemistry, 2020)
Water is a matter of vital importance for all developed countries due to the strong impact on human health and aquatic, wetlands and terrestrial environments. Therefore the monitoring of water quality is of tremendous importance. The enormous advantages that Surface-enhanced Raman scattering (SERS) spectroscopy offers, such as fingerprint recognition, multiplex capabilities, high sensitivity and selectivity or nondestructive testing, make this analytical tool very attractive for monitoring water quality. This minireview will provide an overview of current approaches undertaken for the implementation of SERS sensors in monitoring organic and inorganic pollutants in water. Therefore, we just focused in those works where the SERS applicability in real water matrices is demonstrated. Nevertheless, it is out of the scope of this minireview the description of the theory behind SERS or the discussion of the different categories of SERS substrates or methodologies.